Factors Affecting Utilization of Insecticide Treated Nets in Households Among Children Under Five Years of Age in Kazo Town Council, Kazo District. - Tumwebaze, Rodgers (Kabale University, 2023)
The study was carried on factors affecting utilization of insecticide treated nets in household’s song children under five years of age in Kazo town council, Kazo district. It was based on the owing to find out the socio-economic and cultural factors affecting the utilization of ITNs ~ng children under-five, to identify the institutional factors affecting the utilization of ITNs among children under-five and to establish knowledge of care takers in the utilization of ITNs among children under-five in Kazo Town Council. Methodology: A cross-sectional research design which was both qualitative and quantitative methods for data collection. Approaches were used. Sample size of 92 respondents was -"nsidered which comprised of parents/care takers of under five children and other key informants like, health workers. VHTs and town council health inspector. Information was .:ollected from 92 respondents using questionnaires and interviews. Data was analyzed using SPSS version 21 to generate both descriptive and inferential statistics. Results: The study findings indicate that significant socio-economic factors affect utilization of ITNs within households and these include; gender of the household head (p= .017), age of household head (p = .005), level of education; (p< .001) religion(p = .031), household size(p=0.028), income status(p= .031 ), number of children below 5(p= .002), gender of the child(p = .026), age of the child(p = .001), presence of fever a month before the survey and sleeping arrangement(p = .046). The study also identified significant cultural factors affecting the utilization of ITNs among children under-five years to be; misconceptions about malaria and its prevention(p=.017), cultural beliefs(p= .033), poor perception and attitude(p< .001).The study further identified the institutional factors affecting the utilization of ITNs among children under-five years to be awareness (p=.011), access/availability(p= .012), poor coverage(p .031), level of financial investment in ITN distribution(p = .041) and poor quality nets(p .049). Conclusion: There are significant socio-economic, cultural and institutional factors affecting utilization of insecticide in Kazo Town Council. The study recommended that plans be made to increase the number of free ITN s distributed to households, increase in community education and public awareness on ITN use.